Efficacy of Retromandibular Approach in The Management of Mandibular Subcondyle Fractures: Retromandibular Approach in Mandibular Subcondyle Fractures - Kumar, Ajeet; Hussain, Fida; Raza , Ali; Wahib Asif Zaidi, Syed; Ayub, Tahera; Shoaib, Muhammad (Pakistan Journal of Health Sciences, 2023)
Mandibular condylar fracturing are a common outcome of mandibular trauma. Condylar and subcondylar injuries benefit best from the retromandibular technique, which also offers the greatest exposure to the joint and ascending ramus. Objective: To determine the efficacy of the retromandibular approach in treating condylar fractures with open reduction and internal fixation (ORIF). Methods: A total of 25 subjects with age range 14 to 55 years having unilateral mandibular condylar fractures with disturbed occlusion utilizingretromandibular approach were included in the study. Relevant information was gathered and evaluated. Results: The average age of the sufferer was 31.18 ± 8.17 years and mean duration of fracture was 5.32 ± 0.73 days. There were 21(84%) male patients and 04 (16%) female sufferers. RTA was the most common mode of injury seen among patients (60%). The shattered segments’ anatomic reduction and fixation were successful. The efficacy was 72% on basis of ease of operation and 96% on fracture stability. Conclusion: This technique is effective in term of ease of operation and fracture stability. Scar acceptability can be considered drawback of this procedure